Strategic map for exploring the ocean-world Enceladus. (September 2016) - Sherwood, Brent
Abstract: Among the many "ocean worlds" of our solar system, Enceladus appears unique in its combination of astrobiologically relevant and exploration-worthy attributes: extensive liquid-water ocean with active hydrothermal activity, containing salts and organics expressed predictably into space. The Enceladus south polar plume allows direct access to telltale molecules, ions, isotopes, and potential cytofragments in space. Plume mass spectroscopy and sample return, in situ investigation of surface fallback deposits, direct vent exploration, and eventually oceanographic exploration can all be envisioned. However, building consensus to fund such ambitious exploration hinges on acquiring key new data. A roadmap is essential. It could start with cost-capped onramps such as flythrough analysis of the plume, following up on Cassini measurements with modern instruments; and sample return of plume material for analysis on Earth. A methodical mission sequence in which each step depends on emergent results from prior missions would push in situ oceanographic exploration into the second half of this century. Even for this scenario, prioritization by the next planetary Decadal Survey would be pivotal. Highlights: Exploration of solar-system "ocean worlds" requires a strategic roadmap. Enceladus is a high-priority target, given accessibility of its habitable ocean contents. A series of Enceladus mission classes can make incremental progress on a logical science roadmap. Missions more sophisticated than in situ plume chemistry require advocacy by Decadal Surveys. Vetted concept studies are required by 2019–2020 to influence the next planetary Decadal Survey.